THE SMOOTH MUSCLE CELL : I. In Vivo Synthesis of Connective Tissue Proteins - Ross, Russell (The Rockefeller University Press, 1971)
These studies have examined the ability of smooth muscle cells from developing aorta of the prepubertal rat to utilize amino acids in the synthesis and secretion of connective tissue proteins. Prepubertal rats, previously given either an alcohol carrier or estradiol-17-beta, were each given an intravenous injection of proline-(3)H. The animals were sacrificed after 15 and 30 min, and 4 hr. Light and electron microscope radioautographs of the aortic smooth muscle and of the myometrial cells demonstrated that the aortic cells, in both groups of animals, and the myometrial cells, in the estrogen-stimulated animals, took up the proline and rapidly secreted it in both collagen and elastic fibers within 4 hr. In contrast, the myometrial cells of the nonstimulated animal took up relatively small amounts of proline and retained most of the amino acid within the cells. Electron microscope radioautographs demonstrated that the organelles involved in this activity were the rough endoplasmic reticulum and Golgi complex together with peripheral elements, presumed to be small vesicles. These studies have demonstrated that the smooth muscle cells of the developing aorta and of the estrogen-stimulated myometrium have a capacity to synthesize and secrete proteins associated with the extracellular connective tissue matrix.